Socio-cultural effects of a tourist resort on the local population – BESTandermatt long-term and companion study - Eggerschwiler, Bea Durrer; Störkle, Mario (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2019)
Wherever tourism develops, the local population is involved and affected. The BESTandermatt long-term and companion study described in this article has been investigating the sociocultural and socioeconomic changes provoked by the construction of a tourist resort in Andermatt (Switzerland) since 2008 and shows concerns of inhabitants at all stages of the construction and operation of the resort. In order not only to gain knowledge in the study regarding the subjective perceptions of the 25 respondents, but also to support the population in the process of change, the surveys were combined with activating methods, inherent to a “participatory action research” in which these respondents can influence both the direction and methods of research. After investigation, it appears that this approach promotes standpoints of local social actors in front of tourist officers and the authorities. Processes of development and change shaped in this way strengthen social cohesion and mutual understanding as self-awareness but also confrontation with otherness may enable the people involved to change their perspective.